All‐Silica Submicrometer Colloidosomes for Cargo Protection and Tunable Release. Issue 36 (7th August 2018) - Jiang, Hang; Hong, Liangzhi; Li, Yunxing; Ngai, To
Abstract: Colloidosomes have received considerable attention for the controlled delivery of active ingredients in medicine, agrochemicals, and cosmetics. However, most reported colloidosomes are highly permeable and size is larger than 1 μm. All silica colloidosomes have now been prepared with adjustable size, compact shell and low permeability. Our approach is based on the formation of inverse water‐in‐oil (w/o) emulsions stabilized solely by hydrophobic silica nanoparticles and subsequent locking of the particle at the oil–water interface by a simple sol–gel reaction of silica precursor at room temperature. The colloidosomes obtained display a robust and closed shell, ensuring a long‐term retention of small hydrophilic molecules such as Methylene Blue. Remarkably, unlike all other reported silica colloidosomes, a timely and stepwise release of the encapsulated cargo can be triggered by adding ethanol or surfactant without destroying the capsule shell. Abstract : All‐silica colloidosomes with submicrometer size, a compact shell, and low permeability are fabricated. They ensure a long‐term retention of small hydrophilic molecules. Remarkably, a stepwise release of the encapsulated cargo can be triggered by adding ethanol or surfactant without destroying the capsule shell.